A cross-sectional analysis of developmental trajectories of vocabulary comprehension among children and adolescents with Down syndrome or intellectual disability of undifferentiated aetiology. Issue 2 (2nd April 2016) - Facon, Bruno; Courbois, Yannick; Magis, David
ABSTRACT: Background In this work we sought to expand our knowledge of developmental trajectories of subcomponents of the language systems of individuals with intellectual disability (ID). We aimed to explore how general and relational vocabularies evolve as a function of cognitive level. Method Developmental trajectories of general and relational vocabulary comprehension were compared among typically developing (TD) children and children and adolescents with ID of undifferentiated aetiology (UND) or Down syndrome (DS). Results Comparisons between TD participants and participants with UND showed no interaction between cognitive level and diagnostic status for general vocabulary, and only a very weak interaction for relational vocabulary. Comparisons between TD participants and participants with DS failed to reveal group-specific trajectories. Performance in general vocabulary was higher than in relational vocabulary for participants with UND and DS. Conclusion The developmental trajectories of vocabulary appear to be globally comparable for participants with or without ID.